Who captures whom – Pokémon or tourists? A perspective of the Stimulus-Organism-Response model. (December 2021) - Hsiao, Chun-Hua; Tang, Kai-Yu
Highlights: The use of gamification is an increasing trend in various fields, including tourism. Social influences and media influences are identified as environmental stimuli. Attachment and conformity influence gamers' post-experience behavior. Players' intention to visit Pokémon spots is significantly correlated with their intention to continue playing the game. Findings provide links between the gamification and tourism literature. Abstract: Since its launch in 2016, Pokémon Go has attracted huge numbers of players, causing a boom in this game market. Although it is not as popular as before, from time to time we still find crowds of players gathered in some spots where Pokémon appear. Numerous reports have explored this Pokémon phenomenon; however, the exact reasons for its popularity remain unknown. The purpose of this study is to explore the post-adoption behavior of Pokémon Go players and its influential factors in the gaming and tourism industries. The theoretical model of stimulus-organism-response was drawn on to examine the impact of the environmental stimuli (social influence and media influence) on players' internal organisms, which in turn affect their post-experience responses. Moreover, gender differences were also examined in the hypothetical relationships. A total of 342 valid questionnaires from actual gamers were collected in this study, and data analysis was performed using a structural equation model. The results show that stimulus effects, such as social stimuli (critical mass and social interaction) and media stimuli (content timeliness and media richness), have significant impacts on the players' internal gamified experience (attachment and conformity), which in turn affect their visit intention to catch creatures at certain attractions and to continue playing Pokémon Go. Further, we have also found that players' intention to visit Pokémon spots is significantly correlated with their intention to continue playing the game. Findings provide links between gamification and tourism literature. Further theoretical and managerial implications are provided.